Political culture, democracy and social participation in Brazil: the management of education under debate - Doracy Dias Aguiar de Carvalho (Universidade Federal do Norte do Tocantins, 2023)
This study, of a theoretical-documentary nature, deals with the implications of political culture for the construction process of Brazilian democracy and for social participation in the management of public policies, especially education. Methodologically supported in the critical dialectical perspective the text seeks to demonstrate the advances and setbacks of the process of building democracy, as well as the impasses to social participation resulting from the authoritarian, clientelist and elitist political culture that historically crosses the Brazilian State and the different social institutions. The study highlights the advances achieved with the 1988 Constitution, as well as the setbacks operated as a result of the neoliberal logic deepened in the government of Michel Temer and Jair Bolsonaro in order to weaken social participation and democratic control in the scope of public policies, such as education. However, it also shows that despite the setbacks that have occurred in this scope, the social participation remains alive and the fight for the strengthening and expansion of participatory democracy has been happening in opposition to the logic of the destruction of the Brazilian participatory heritage built over the last 30 years.